Far from Fire: The service delivery quality gap plaguing Indonesian Ports - Wayu Eko Yudiatmaja; Alfiandri Alfiandri; Rahmat Hidayat (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2017)
This study analyzes the gap between expected and perceived services by ship passengers at the Sri Bayintan Port, Kijang, Riau Archipelago. The purpose of the paper is to examine the gap between expected and perceived service delivery by ship passengers in the Sri Bayintan Port.  To test the service gap, ServQual variables as postulated in Parasuraman, Zeithaml & Berry (1988) were used. The variables include tangibility, reliability, responsiveness, assurance, and empathy. Data were collected using a sample of 98 passengers, who were chosen at random. Research results showed that there is a significant difference between expected and perceived service delivery among   passengers who use Sri Bayintan port.  In particular, findings of this study showed that passengers were not satisfied with the quality of service delivery they received in Sri Bayintan Port.